2022
DOI: 10.3389/fphar.2022.872474
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenoside Rb1 Ameliorated Bavachin-Induced Renal Fibrosis via Suppressing Bip/eIF2α/CHOP Signaling-Mediated EMT

Abstract: The nephrotoxicity of Fructus Psoraleae, an effective traditional Chinese medicine for vitiligo treatment, has been reported. As one of the main toxic components in Fructus Psoraleae, bavachin (BV) was considered to be related to Fructus Psoraleae-caused adverse outcomes, but the direct evidence and molecular mechanism underlying BV-induced nephrotoxicity are not well elucidated. Therefore, this study was designed to confirm whether BV would cause toxic effects on the kidney and explore the possible mode of ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…However, in the case of oral herbal remedies, therapeutic compounds are more likely to be found in the blood of patients and animals who have consumed them [31]. Previous research has also shown that Ginsenoside Rb1 and Salvianolic Acid D not only protect against renal fibrosis but are also linked to the restoration of mitochondrial function [32][33][34]. Additionally, Dimethylcurcumin and curcumenol have demonstrated efficacy in treating renal disorders [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…However, in the case of oral herbal remedies, therapeutic compounds are more likely to be found in the blood of patients and animals who have consumed them [31]. Previous research has also shown that Ginsenoside Rb1 and Salvianolic Acid D not only protect against renal fibrosis but are also linked to the restoration of mitochondrial function [32][33][34]. Additionally, Dimethylcurcumin and curcumenol have demonstrated efficacy in treating renal disorders [35,36].…”
Section: Discussionmentioning
confidence: 99%
“… 96 In other disease models, ginsenoside Rb1 inhibited ROS generation and overactivated ERS, and decreased cytoplasmic Ca2+ release to ameliorate renal fibrosis. 97 In addition, narrow‑band ultraviolet B phototherapy is effective in treating vitiligo. 98 The current study found that combined NB-UVB and adipose‑derived stem cell transplantation was beneficial to MBZ-induced vitiligo mice.…”
Section: Clinical Treatmentsmentioning
confidence: 99%
“…In addition, the possible protective effects and mechanisms of ginsenoside Rb1 on oxidative damage and renal interstitial fibrosis in rats with unilateral ureteral obstruction (UUO) have been widely studied. Fan et al found that ginsenoside Rb1 significantly inhibited renal interstitial fibrosis in UUO rats by down-regulating TGF-β1 ( Xie et al 2009 ) expression or ihibiting Bip/eIF2α/CHOP signaling-mediated EMT ( Ni et al 2022 ). There are reports that ginsenoside Rb1 treats acute kidney injury by activating the Nrf2/ARE pathway which acts against oxidative stress ( Sun et al 2012 ).…”
Section: Application Of Ginsenosides In Kidney Related Diseasesmentioning
confidence: 99%